2019
DOI: 10.1111/ele.13228
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of habitat continuity for delimiting biogeographic regions and shaping richness gradients

Abstract: The formation and maintenance of biogeographic regions and the latitudinal gradient of species richness are thought to be influenced, in part, by the spatial distribution of physical habitat (habitat continuity). But the importance of habitat continuity in relation to other variables for shaping richness gradients and delimiting biogeographic regions has not been well established. Here, we show that habitat continuity is a top predictor of biogeographic structure and the richness gradient of eastern Pacific ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…In the marine environment, global climatic changes often cause a shift in the geographic distribution and abundance of species (Rivadeneira & Fernández 2005; Parmesan, 2006; Mieszkowska & Sugden, 2016; Sanda et al ., 2019). The fauna of the rocky intertidal zone is an excellent model to investigate the impacts of global change on biota since the ecosystem is common worldwide, although it can be patchy in the Tropical Eastern Pacific compared with temperate East Pacific regions (Fenberg & Rivadeneira, 2019). For intertidal invertebrates, the rocky shore is a harsh habitat with strong selection pressure from both physical (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the marine environment, global climatic changes often cause a shift in the geographic distribution and abundance of species (Rivadeneira & Fernández 2005; Parmesan, 2006; Mieszkowska & Sugden, 2016; Sanda et al ., 2019). The fauna of the rocky intertidal zone is an excellent model to investigate the impacts of global change on biota since the ecosystem is common worldwide, although it can be patchy in the Tropical Eastern Pacific compared with temperate East Pacific regions (Fenberg & Rivadeneira, 2019). For intertidal invertebrates, the rocky shore is a harsh habitat with strong selection pressure from both physical (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the latitudinal diversity gradient is biogeographically structured [45], and since the above investigations were conducted in a temperate biogeographic region, a gradients might not occur. For example, while gastropod richness is relatively stable in the temperate region, a steep rise in richness occurs in the tropical region [23]. However, the few published global-scale studies have revealed contradictory latitudinal patterns with richness of macroalgae [26] and small echinoderms peaking at high latitudes, while large echinoderms peak at low latitudes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Intertidal shores rank as one of the most studied marine habitats, and are often seen as harbingers for the effects of climate change and invasive species [22]. Regional-scale intertidal studies have found richness gradients of gastropods along coastlines in the eastern Pacific Ocean [23,24]. However, no latitudinal diversity gradient of gastropods [25] or macroalgal [26] was found on a global-scale across oceans, and assembly-wide studies have found missing [27][28][29] or inverse [30] gradients.…”
Section: Introductionmentioning
confidence: 99%
“…). Suitable rocky substratum was defined as coastline stretch composed of rocks of different area extending from coastal rock outcrops to the outermost rocks, excluding sandy beaches or other soft‐sediment habitats, such as river deltas (Fenberg and Rivadeneira ). From a biogeographic viewpoint, the study area lies within the so‐called Intermediate Area (30° S–42° S), where the biogeographic ranges of multiple taxa of the warm‐temperate Peruvian province and the cold‐temperate Magellan province coexist (Camus ).…”
Section: Methodsmentioning
confidence: 99%